2019
DOI: 10.1002/jbm.a.36801
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics of electrospinning PTH‐Fc/PLCL/SF membranes for bioengineering applications

Abstract: Alveolar bone loss is always a big challenge for oral implant placement. Guided bone regeneration (GBR) is one of the solutions to fix this problem. Among all the factors, the barrier membrane plays a key role in this technology. At present, lack of the osteoinductivity remains the biggest weakness for clinical application. Focusing on this, we tried to fabricate an osteoinductive three-dimensional (3D) nanofiber membrane with drug releasing system by introducing parathyroid hormone (PTH)-Fc into the poly(lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Generally, the biphasic pattern of initial burst release and subsequent steady release was a typical release profile observed in ordinary electrospinning groups. Most studies about drugs or osteogenic factors-loaded electrospun membranes 5861 reported good osteogenic properties of their developed membranes. While the release rate and total release have an influence on the osteogenic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the biphasic pattern of initial burst release and subsequent steady release was a typical release profile observed in ordinary electrospinning groups. Most studies about drugs or osteogenic factors-loaded electrospun membranes 5861 reported good osteogenic properties of their developed membranes. While the release rate and total release have an influence on the osteogenic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Several new methods have been developed to provide more convenient and effective ways to apply PTH or PTHrP as well as to reduce side effects. Among the various delivery methods proposed are an implantable and biodegradable pulsatile device ( Dang et al, 2017 ), bio-membrane fabrication ( Yin et al, 2020 ), and a nanoemulsion system ( Altaani et al, 2020 ). Most of the current research has not progressed beyond the pre-clinical phase, thus detailed guidance for dosage, frequency, duration, and clinical indication of PTH or PTHrP administration in orofacial region is still required.…”
Section: Therapeutic Application Of Parathyroid Hormone/parathyroid Hormone-related Protein In Orofacial Regionmentioning
confidence: 99%
“…Fibrous scaffolds prepared by electrospinning are capable of mimicking the complex structure of a natural extracellular matrix ( Hasan et al, 2014 ; Ingavle and Kent, 2014 ; Kishan and Hernandez, 2017 ; Zong et al, 2018 ; Eilenberg et al, 2020 ), and they have large specific surface areas and a high-porosity microstructures that facilitate cell and nutrient infiltration ( Yin et al, 2020a ; Guo et al, 2022 ). The method of coaxial electrospinning can prepare functional fiber membranes ( Ezhilarasu et al, 2019 ; Johnson et al, 2021 ; Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%